The Effects on Output of Money Growth and Interest Rate Volatility in the United States - Evans, Paul (Journal of Political Economy, 1984)
In October 1979, the Federal Reserve began a policy of disinflation and also stopped stabilizing interest rates. Subsequently, interest rates became much more volatile. Using a methodology advanced by Barro, this paper estimates what this change in policy did to output in the United States. The paper finds that the stagnation of the U.S. economy since 1979 stemmed almost as much from increased interest rate volatility as from reduced money growth. The paper also assesses the extent to which increased volatility of money growth has contributed to stagnation. It finds no evidence of any appreciable contribution. The paper concludes that stabilizing interest rates is probably sensible monetary policy.